Uso del tomógrafo para determinar sanidad en plantación forestal de tornillo en el Dorado – INIA, distrito de San Juan Bautista, Loreto, 2022 - Muñoz Schrader, Ornella Lorena (2023)
The Peruvian Amazon has a high level of biodiversity and is the fifth most deforested region in the world; forest plantations are one measure to curb this problem. Generally, businessmen and timber producers select harvestable trees using visual methods based on external morphological characteristics, without taking into account the internal health of the individuals. Therefore, in order to promote and contribute to forestry development, the main objective of this study is to use the acoustic tomograph to determine the internal health of a forest plantation of Tornillo in El Dorado - INIA, District of San Juan Bautista, Loreto. The plantation is 24 years old and consists of 40 individuals of Cedrelinga cateniformis (Ducke) Ducke. The biometric structure and health (internal and external) were evaluated, using equipment such as Field-Map and acoustic tomograph. The dasometric variables showed high heterogeneity, with greater variability for basal area, total and commercial volume. Likewise, the plantation showed mean annual increases in DBH and total height of 2,1 cm/year and 1,2 m/year, respectively. The external part of the trees showed a 60% incidence of lichen damage and at the level of internal health the incidence of internal attack was 92,5%; the wood was minimally affected, located mainly in the basal and peripheral parts. Acoustic tomography, a non-destructive equipment, proved its effectiveness in the evaluation of the internal health of individual tornillo trees in forest plantations.